2012
DOI: 10.1002/mrc.3815
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐state 11B and 13C NMR, IR, and X‐ray crystallographic characterization of selected arylboronic acids and their catechol cyclic esters

Abstract: Nine arylboronic acids, seven arylboronic catechol cyclic esters, and two trimeric arylboronic anhydrides (boroxines) are investigated using (11)B solid-state NMR spectroscopy at three different magnetic field strengths (9.4, 11.7, and 21.1 T). Through the analysis of spectra of static and magic-angle spinning samples, the (11)B electric field gradient and chemical shift tensors are determined. The effects of relaxation anisotropy and nutation field strength on the (11)B NMR line shapes are investigated. Infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 50 publications
3
21
0
Order By: Relevance
“…However, the field remains relatively unexplored, with only limited applications to boron‐containing functional groups that are of interest in pharmaceutical discovery outside of boronic acids. A study of arylboronic acids, arylboronic catechol cyclic esters, and aryl boroxines showed good agreement between experimental and calculated EFG and NMR shielding parameters using the GIPAW method with the PBE functional and plane wave cutoffs similar to those used here . This method also performed well in the present work, as observed by the results in Table , suggesting that this may be an accurate approach for future studies of organoboron pharmaceuticals in addition to the aforementioned HCTH/DNP level of theory using the DMol3 package.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…However, the field remains relatively unexplored, with only limited applications to boron‐containing functional groups that are of interest in pharmaceutical discovery outside of boronic acids. A study of arylboronic acids, arylboronic catechol cyclic esters, and aryl boroxines showed good agreement between experimental and calculated EFG and NMR shielding parameters using the GIPAW method with the PBE functional and plane wave cutoffs similar to those used here . This method also performed well in the present work, as observed by the results in Table , suggesting that this may be an accurate approach for future studies of organoboron pharmaceuticals in addition to the aforementioned HCTH/DNP level of theory using the DMol3 package.…”
Section: Resultssupporting
confidence: 76%
“…A study of arylboronic acids, arylboronic catechol cyclic esters, and aryl boroxines showed good agreement between experimental and calculated EFG and NMR shielding parameters using the GIPAW method with the PBE functional and plane wave cutoffs similar to those used here. 55 This method also performed well in the present work, as observed by the results in Table 2, suggesting that this may be an accurate approach for future studies of organoboron pharmaceuticals in addition to the aforementioned HCTH/DNP level of theory using the DMol3 package. The role of intermolecular effects on 11 B quadrupolar parameters can also be investigated using the GIPAW calculations.…”
Section: B Ssnmr Analysissupporting
confidence: 77%
See 2 more Smart Citations
“…From the FTIR spectrum of PTBA (Figure b) it was clearly seen that peaks arising from  OH stretching of boronic acid group were observed at 3499 cm −1 and the C  H stretching band of aromatic thiophene ring was observed at 3103 cm −1 . C=C and C  C bonds in the aromatic ring at 1670, 1522, and 1398 cm −1 , respectively, were attributed to the extension of the conjugations when compared to the monomer and supported the successful polymerization.…”
Section: Resultsmentioning
confidence: 70%